2020
DOI: 10.3390/cancers12051130
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Hepatocellular Carcinoma in Renal Insufficiency: Prognostic Role of Albumin-Bilirubin Grade

Abstract: Renal insufficiency (RI) is commonly seen in patients with hepatocellular carcinoma (HCC). The prognostic role of albumin-bilirubin (ALBI) grade in this special setting is unclear. We aimed to investigate the role of ALBI grade associated with the impact of RI on HCC. A prospective cohort of 3690 HCC patients between 2002 and 2016 were retrospectively analyzed. The Kaplan–Meier method and multivariate Cox proportional hazards model were used to determine survival and independent prognostic predictors. Of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The CTP classification and MELD score are used to evaluate the severity of liver injury. However, these two models were reported to have some shortcomings 28 . Recently, ALBI grade is a simple and objective indicator to assess the severity of liver damage in HCC patients and has been validated by several research groups 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The CTP classification and MELD score are used to evaluate the severity of liver injury. However, these two models were reported to have some shortcomings 28 . Recently, ALBI grade is a simple and objective indicator to assess the severity of liver damage in HCC patients and has been validated by several research groups 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The ALBI score is calculated using the following equation as previously defined: 11,13,22 ALBI score = 0.66 � log 10 bilirubin (μmol/L) − 0.085 � albumin (g/L).…”
Section: Albumin-bilirubin Score and Gradingmentioning
confidence: 99%
“… 21 , 22 In addition, several epidemiological surveys and experimental studies have shown that the risk of death from HCC was significantly associated with mass size, the number of masses, macrovascular invasion, and intrahepatic metastases; thus, suggesting that hepatocarcinogenesis is influenced by genetic factors. 23–25 …”
Section: Current Status Of Liver Cancer Treatmentmentioning
confidence: 99%